Fintech Lending Tax Planning Strategy Based on Indonesian Taxation Rules - Nafis Dwi Kartiko; Ismi Fathia Rachmi (Activa Yuris: Jurnal Hukum, 2021)
Technology is a necessary component of life and has an effect on it. The existence of technology has pushed the economy in a digital direction, which is continuing to grow. This trend is being felt across the economy, including the financial services sector. Fintech is one of the technological advancements in the financial services industry. Indonesia's fintech regulations are less complex than those in other countries. One of the regulatory flaws manifests itself in the area of taxation. As a result, fintech companies must develop a tax planning strategy. The purpose of this paper is to examine tax planning strategies for fintech lending through the lens of qualitative-descriptive research methods. The analysis is based on Indonesia's current legal provisions. The researchers developed tax planning strategies specifically for corporate income tax and value-added tax. The researchers concluded as follows based on the findings of the current regulation study: (1) in terms of value-added tax, fintech lending should pay attention to the limitations of taxable entrepreneurs, the separation of taxable and incentive income, as well as ensuring that input tax credit works properly; and (2) ensure that taxes withheld by third parties are appropriate and have a purpose.